Partnerships in mathematics and science teacher preparation in Zimbabwe - Alois Matorevhu (Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
Research evidence indicates that collaborative partnerships among stakeholders develop strong sense of ownership, interest and commitment, which promotes successful programme implementation. Research evidence also supports that loose partnerships adversely affect programme implementation. This study sought to explore the nature of partnerships among teacher education stakeholders in the pre–service Diploma in Education programme, offered at Teachers’ College S which is an associate of the University of Zimbabwe. Interviews with mentor teachers, pre-service teachers on attachment teaching practice/practicum, and head teachers were used to generate and collect data. Findings revealed existence of collaborative partnerships among Teachers’ College S, schools and the University of Zimbabwe. However, most mentor teachers expressed concern on absence of a policy guiding their operations. Recommendations to strengthen collaborative partnerships in pre–service teacher preparation were made.